RELEVANSI KOMPETENSI LULUSAN TATA BOGA YANG DIBUTUHKAN PADA HOTEL BERBINTANG DI KOTA MAKASSAR - Siti Nur Elli B; H. Husain Syam; Nahriana (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2024)
This research aims to; (1) to determine the culinary work skills required by hotels in the city of Makassar, (2) to determine the level of relevance of culinary work competencies to hotels in the city of Makassar. This type of research includes quantitative descriptive research with survey methods. This research uses quantitative descriptive statistical data analysis techniques with percentages. The results of this research show that; 1) A total of 32 basic competencies with a percentage of 100% are really needed by the Four Point By Sheraton Hotel Makassar, Swiss-Bel Hotel Makassar, and the Aston Hotel and Convention Center Makassar. (2) the level of relevance of work competency in the relevant category is 97.22%. (3) 2.78% or 22 work competencies were obtained that were irrelevant or not needed in several hotels.